(untitled) (Quinto Sol, 2015)
Two central aspects of ecclesiastical construction in the Argentine Confederation during the 1850s are analyzed: the financing of the cult by the State and the provision process of all its dioceses. An attempt is made to show that, in that construction, the State and the Holy See functioned more as spaces of confluence of specific actors, than as actors themselves. This hypothesis is linked to new approaches to the formation of the national state and to Romanization.